2021
DOI: 10.3390/jcm10194382
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Morbid Obesity on the Health Outcomes of Hospital Inpatients: An Observational Study

Abstract: Morbid obesity poses a significant burden on the health-care system. This study determined whether morbid obesity leads to worse health-outcomes in hospitalised patients. This retrospective-study examined nutritional data of all inpatients aged 18–79 years, with a body-mass-index (BMI) ≥ 18.5 kg/m2 admitted over a period of 4 years at two major hospitals in Australia. Patients were divided into 3 groups for comparison: normal/overweight (BMI 18.5–29.9 kg/m2), obese (BMI 30–39.9 kg/m2) and morbidly-obese (BMI ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
5
1
1
Order By: Relevance
“…Furthermore, while propensity score analysis was used to address potential confounding factors and minimize bias, there may still be unmeasured confounding factors that could affect the outcomes. Unmeasured confounding may be evident in the current study wherein patients with and without morbid obesity demonstrated similar hospital and ICU lengths of stay, as well as similar durations of BL/BLI therapy, even though patients in the morbid obesity group had a significantly higher rate of presumed treatment failure, which differs from previous data [ 3 , 48 , 49 ]. Another possible limitation is our use of a composite endpoint to improve the ability to detect differences in the primary outcome between groups; however, we did report individual endpoints in the primary outcome for clarity and conducted a power analysis based on available data.…”
Section: Discussioncontrasting
confidence: 85%
“…Furthermore, while propensity score analysis was used to address potential confounding factors and minimize bias, there may still be unmeasured confounding factors that could affect the outcomes. Unmeasured confounding may be evident in the current study wherein patients with and without morbid obesity demonstrated similar hospital and ICU lengths of stay, as well as similar durations of BL/BLI therapy, even though patients in the morbid obesity group had a significantly higher rate of presumed treatment failure, which differs from previous data [ 3 , 48 , 49 ]. Another possible limitation is our use of a composite endpoint to improve the ability to detect differences in the primary outcome between groups; however, we did report individual endpoints in the primary outcome for clarity and conducted a power analysis based on available data.…”
Section: Discussioncontrasting
confidence: 85%
“…Although identification and management of undernutrition is an issue in hospitals, for many hospitalized patients addressing the nutrition problem of obesity will benefit health outcomes. Studies have found having morbid obesity leads to worse health outcomes, including longer lengths of hospital stays [ 12 , 13 , 15 , 17 ] and increased risk of hospital complications [ 17 , 18 , 41 ], including infection post-surgery [ 15 ]. In addition, patients who have obesity are more likely to be admitted to the Intensive Care Unit post-trauma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, overweight and obesity contributed 8.4% to the burden of diseases, second only to tobacco use (9.3%). Obesity is associated with both greater duration and cost of hospitalization [ 11 ], with significant differences in the average length of stay found for almost all medical and surgical specialties for patients who have obesity [ 2 , 12 , 13 ]. Patients who have obesity have higher complications post-surgery [ 14 , 15 ], are at risk of skin breakdown and impaired wound healing [ 16 ], increased rates of infection and sepsis [ 11 , 15 , 17 , 18 ], have a greater chance of admission to the intensive care unit [ 17 ], and an increased risk of morbidity [ 18 ] and mortality [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…En este estudio se encontró que casi el 25 % de los pacientes tenían un IMC por arriba de 25, siendo casi la mitad que, en otro estudio realizado en Paraguay ; y ligeramente inferior a otro, realizado en Perú. No obstante, otros estudios analíticos y metaanálisis no han encontrado una asociación entre la obesidad y la incidencia de ACV isquémicos (25)(26)(27)(28).…”
Section: Localización N (%)unclassified